2004
DOI: 10.1007/s00262-004-0593-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of PD-L1 on tumor cells with PD-1 on tumor-specific T cells as a mechanism of immune evasion: implications for tumor immunotherapy

Abstract: Programmed death receptor ligand 1 (PD-L1, also called B7-H1) is a recently described B7 family member. In contrast to B7-1 and B7-2, PD-L1 does not interact with either CD28 or CTLA-4. To date, one specific receptor has been identified that can be ligated by PD-L1. This receptor, programmed death receptor 1 (PD-1), has been shown to negatively regulate T-cell receptor (TCR) signaling. Upon ligating its receptor, PD-L1 has been reported to decrease TCR-mediated proliferation and cytokine production. PD-1 gene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
396
0
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 539 publications
(413 citation statements)
references
References 72 publications
6
396
0
11
Order By: Relevance
“…60 In addition, PD-L1 was reported to be expressed on a wide variety of murine and human tumors, either constitutively or upon exposure to IFN-g. 22,42,53,64 Tumor-associated PD-L1 has been shown in animal models to inhibit antitumoral T cell responses, 20 implying PD-L1 to play a pivotal role in tumor evasion from antitumor immune responses. 20,53,65 Furthermore, it has been shown that activated T cells also express PD-L1, raising the possibility of self-restriction of an antitumor T cell response during the priming phase. 22,66 We thus addressed, in our study, the question at which stages and under which conditions of induction and effector phases of human tumor-specific T cell responses the addition of neutralizing anti-PD-L1 mAb might be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…60 In addition, PD-L1 was reported to be expressed on a wide variety of murine and human tumors, either constitutively or upon exposure to IFN-g. 22,42,53,64 Tumor-associated PD-L1 has been shown in animal models to inhibit antitumoral T cell responses, 20 implying PD-L1 to play a pivotal role in tumor evasion from antitumor immune responses. 20,53,65 Furthermore, it has been shown that activated T cells also express PD-L1, raising the possibility of self-restriction of an antitumor T cell response during the priming phase. 22,66 We thus addressed, in our study, the question at which stages and under which conditions of induction and effector phases of human tumor-specific T cell responses the addition of neutralizing anti-PD-L1 mAb might be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that T cells specific to mHA expressed by both tumor cells and healthy tissues of bone marrow-transplanted recipients might not be able to mediate antileukemia effect. This is particularly relevant if one considers the major importance of PD-L1 tumor cell expression in the phenomenon of immune evasion (47).…”
Section: Figurementioning
confidence: 99%
“…However, multiple regulatory mechanisms that blunt T cell function within the tumor microenvironment arise in tumors (27). Programmed death ligand 1 (PD-L1), an inhibitory molecule frequently upregulated on tumor cells, is one of the major immunological checkpoints contributing to tumor-immune escape (28) through the inhibition of T cell activation and promotion of apoptosis of DCs (29) and CD8 + T cells (30). In several clinical trials, blockade of programmed death-1 (PD-1) or PD-L1 resulted in enhanced T cell function and improved immune-mediated tumor control (31).…”
mentioning
confidence: 99%